2014 International Conference on Interactive Collaborative Learning (ICL) 2014
DOI: 10.1109/icl.2014.7017830
|View full text |Cite
|
Sign up to set email alerts
|

Project based learning: Real world experiential projects creating the 21st century engineer

Abstract: Industry throughout the world are demanding engineering graduates that are better prepared to support their organizations. Project based learning (PBL) is being recognized as a pedagogical approach that gives engineering students an opportunity to learning by doing and applying their training to real world problems. PBL is implemented in many different styles. This paper describes one of the themes of PBL-the gradual transition from solving closed ended problems to addressing real world open ended problems. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 4 publications
0
12
0
2
Order By: Relevance
“…Apart from academic mobility, universities practice intersectoral mobility when doctoral programs are implemented in collaboration with industrial partners who provide temporary placement for doctoral students in applied research programs. Thus, they can participate in real world experiential projects (Sanger & Ziyatdinova, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Apart from academic mobility, universities practice intersectoral mobility when doctoral programs are implemented in collaboration with industrial partners who provide temporary placement for doctoral students in applied research programs. Thus, they can participate in real world experiential projects (Sanger & Ziyatdinova, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Various research findings have shown that the traditional methods being practiced in Nigerian institutions of learning are obsolete and far from meeting the skills need of the 21 st century, 4 th industrial revolution and the needs of the present society [41], [43], [44].…”
Section: Impact Of Nigerian Conventional Teaching Methods On the mentioning
confidence: 99%
“…Unlike traditional classroom practices that are short and teacher-centered, project based learning emphasizes learning activities that are long term, student-centered, and integrated with real world issues and real life practices. Incorporation of real-world projects into the classroom provides a unique and priceless enhancement to the educational experience [33]. Project-based learning involves a series complex tasks which engages students by working on open-ended projects, problem-solving, decision making, or investigative activities.…”
Section: Project-based Learningmentioning
confidence: 99%